Guatemala : Investment Climate Assessment, Volume 2. Background Notes on Productivity - World Bank (Washington, DC, 2012)
Guatemala has achieved substantial progress in improving its investment climate since 2004. Despite these achievements, Guatemala continues to face significant challenges. Guatemala's overall ease of doing business ranking is still relatively low-114th out of 178 countries, and it falls well behind the rankings of comparator countries such as El Salvador (69), Nicaragua (93), and Panama (65). Economic growth in Guatemala over the past 25 years has been very modest, even by Latin American standards. Productivity and export growth has been disappointing. The Central America Free Trade Agreement (CAFTA) brings new opportunities as well as competitive pressures. To be competitive, Guatemala needs to aggressively tackle reforms in three main areas: infrastructure, governance, and access to finance. Reforms in these areas, as well as other targeted initiatives, will better position Guatemala to take advantage of CAFTA. The Government should also build on what has been working in trade promotion. Road, port, and airport quality could all be improved, with private sector participation playing a key role. Electricity subsidies should be targeted in a more efficient manner and the social tariff system should be reconsidered. More effective mechanisms to promote investments in renewable energy should be adopted. Guatemala should continue reforming its regulation of private business activity-especially in firm registration, construction permits, and tax and customs administration. The government should attack corruption directly. Concerted, long-term effort is needed to strengthen contract enforcement and the judiciary. To lower crime, the strategy should be to emphasize preventive measures and support greater police enforcement. The growth of commercially oriented microfinance institutions (MFIs) should be promoted through an adequate regulatory and supervisory framework. Accounting and auditing practices, financial information infrastructure, and regulatory norms for movable collateral should be strengthened.